Neutralization of the edema-forming, defibrinating and coagulant effects of Bothrops asper venom by extracts of plants used by healers in Colombia - Núñez,V. (2004)
We determined the neutralizing activity of 12 ethanolic extracts of plants against the edema-forming, defibrinating and coagulant effects of Bothrops asper venom in Swiss Webster mice. The material used consisted of the leaves and branches of Bixa orellana (Bixaceae), Ficus nymphaeifolia (Moraceae), Struthanthus orbicularis (Loranthaceae) and Gonzalagunia panamensis (Rubiaceae); the stem barks of Brownea rosademonte (Caesalpiniaceae) and Tabebuia rosea (Bignoniaceae); the whole plant of Pleopeltis percussa (Polypodiaceae) and Trichomanes elegans (Hymenophyllaceae); rhizomes of Renealmia alpinia (Zingiberaceae), Heliconia curtispatha (Heliconiaceae) and Dracontium croatii (Araceae), and the ripe fruit of Citrus limon (Rutaceae). After preincubation of varying amounts of each extract with either 1.0 µg venom for the edema-forming effect or 2.0 µg venom for the defibrinating effect, the mixture was injected subcutaneously (sc) into the right foot pad or intravenously into the tail, respectively, to groups of four mice (18-20 g). All extracts (6.2-200 µg/mouse) partially neutralized the edema-forming activity of venom in a dose-dependent manner (58-76% inhibition), with B. orellana, S. orbicularis, G. panamensis, B. rosademonte, and D. croatii showing the highest effect. Ten extracts (3.9-2000 µg/mouse) also showed 100% neutralizing ability against the defibrinating effect of venom, and nine prolonged the coagulation time induced by the venom. When the extracts were administered either before or after venom injection, the neutralization of the edema-forming effect was lower than 40% for all extracts, and none of them neutralized the defibrinating effect of venom. When they were administered in situ (sc at the same site 5 min after venom injection), the neutralization of edema increased for six extracts, reaching levels up to 64% for C. limon.